Reaction of lima bean genotypes to Macrophomina phaseolina - García,Mynor Efraín Munguía (2019)
ABSTRACT Charcoal rot, caused by Macrophomina phaseolina, is an important disease of lima bean (Phaseolus lunatus L.) in the Northeast of Brazil. Considering that there are no reports of resistance to this disease in Brazil, 37 lima bean accessions were evaluated for their resistance reaction and resistance stability against isolates of M. phaseolina in two periods of the year (February-March and July-August 2016), with the aim of selecting genotypes with the potential for use in the management of this disease. Seeds were inoculated at sowing, using rice grains with husk that were colonized by the pathogen. The evaluations of genotypes were carried out at every five days, from the tenth day after sowing, using a score scale and dividing them into six reaction classes. From a population of 37 accessions of P. lunatus, no immunity reaction to M. phaseolina was seen; however, thirteen accessions presented the lowest severity levels and greatest stability in the two seasons: UFPI 892, UFPI 908 and UFPI 905, which were considered resistant to the isolate COUFPI 06. The resistance reaction of accessions considered resistant varied depending on the isolate of M. phaseolina. Accession UFPI 908 expressed the most promising results for resistance and stability of resistance against the isolates COUFPI 06, COUFPI 08 and COUFPI 10. Therefore, accession UFPI 908 constitutes a promising source of resistance to M. phaseolina, making possible its use in breeding programs and in integrated management of charcoal rot.